(untitled) (المجلة الدولية للبحوث العلمية, 2026)
This study investigates the practical agricultural application of hydrogen peroxide (H₂O₂) as a growth-promoting and stress-mitigating agent in crop production. The experiment aimed to evaluate the effects of different concentrations of hydrogen peroxide on plant growth parameters under controlled greenhouse conditions. Tomato plants (Solanum lycopersicum) were used as a model crop, and four treatments were applied: control (0% H₂O₂), 0.5%, 1.0%, and 1.5% hydrogen peroxide solutions. The experimental procedure involved seed planting in standardized soil mixtures followed by periodic application of hydrogen peroxide solutions as foliar spray and soil drench over a four-week period. Plant growth indicators including plant height, number of leaves, root length, biomass accumulation, and soil pH were measured and analyzed statistically. The results showed that moderate concentrations of hydrogen peroxide significantly improved plant growth compared with the control treatment. Plants treated with 1.0% H₂O₂ exhibited the highest plant height, leaf number, root length, and biomass accumulation. The findings suggest that low to moderate concentrations of hydrogen peroxide may enhance plant growth by improving oxygen availability in the root zone and stimulating physiological processes such as photosynthesis and nutrient uptake. However, higher concentrations showed reduced growth performance, indicating the importance of controlled application. The study concludes that hydrogen peroxide can serve as a practical and cost-effective agricultural treatment when applied at appropriate concentrations. Further field studies are recommended to evaluate its long-term effects on crop productivity and soil ecosystems.